Missing Midwifery: Relevance for Contemporary Challenges in Maternal Health - Rupa Prasad; Rajib Dasgupta (Wolters Kluwer Medknow Publications, 2013)
Midwifery is rooted in public health, and most of its history has been community oriented. In India, midwifery evolved during the British rule; but over the years with changes in political and program priorities, the role and the capacity of midwives has changed substantially. The verticalization of national health programs has obscured the midwives' community focus and inhibited its contribution to the wider public health. There is a global acceptance and recognition of the midwifery model of care and skilled delivery for ensuring effective maternal health outcomes. The approaches are in line with local needs and have proved its effectiveness in resource-constrained settings. It is important to recognize the substantial contribution they make to public health, working to promote the long-term well-being of women, their babies and families, by offering information and advice on nutrition, supplementation, breastfeeding, and immunization. There is considerable scope for developing the midwifery model through enhancing the extent of their involvement in assessing health needs of local populations, designing, managing and evaluating maternal and health services, making timely and effective referrals and developing family-centered care.